Carbon-free dry reforming of methane to syngas over NdCoO3 perovskite-type mixed metal oxide catalyst - Choudhary, Vasant R.; Mondal, Kartick C.; Mamman, Ajit Singh; Joshi, Upendra A. (Catalysis Letters, 2005)
CoNdOx (Co/Nd = 1) is a highly promising catalyst for the carbon-free CO2 reforming of methane. Influence of the Co/Nd ratio on the catalyst performance in the CO2 reforming and also on the crystalline phases and reduction by temperature programmed reduction (TPR) of the CoNdOx catalyst has also been investigated. The CoNdOx (CoNd = 1.0) catalyst consisted of mainly NdCoO3 perovskite- type mixed metal oxide and it showed not only a high resistance to carbon formation at different process conditions ( viz. temperature = 750 - 900 degrees C and gas hourly space velocity (GHSV) = 10000 - 50000 cm(3) g(-1) h(-1)) but also high activity and selectivity in the CO2 reforming process. The high resistance to carbon formation for this catalyst is attributed mostly to strong metal (Co degrees) - support (Nd2O3) interactions.
Keywords: CO2 reforming of methane to syngas; CoNdOx catalyst; NdCoO3 perovskite; resistance to carbon formation in CO2 reforming

High-temperature stable and highly active/selective supported NiCoMgCeOx catalyst suitable for autothermal reforming of methane to syngas - Choudhary, Vasant R.; Mondal, Kartick C.; Mamman, Ajit Singh (Journal of Catalysis, 2005)
Low-surface-area, macroporous, zirconia-haffnia-supported NiCoMgOx and NiCoMgCeOx (Ni/Co/Mg/Ce = 1/0.2/1.2/0.0 or 1.2) catalysts, precalcined at high temperature ( 1400 degrees C for 4 h), showed both high activity (> 98% conversion) and selectivity ( > 95%) in the catalytic partial oxidation of methane (CPOM) to syngas. Their performance remained unchanged even after they were subjected to higher temperature (> 2000 degrees C for 30 min) or a number of high-temperature (> 2000 degrees C) shocks, due to their direct exposure to an oxyacetylene flame. The supported NiCoMgCeOx, however, showed superior performance in the steam and CO2 reforming reactions because of its much higher lattice oxygen mobility. Hence it is more suitable for the autothermal reforming of methane. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: autothermal reforming of methane; Catalyst; catalytic partial oxidation of methane; CO2 reforming of methane; high-temperature stable supported NiCoMgCeOx catalyst; steam reforming of methane; zirconia-haffnia-supported NiCoMgCeOx catalysts; zirconia-haffnia-supported NiCoMgOx

Furfural: hemicellulose/xylosederived biochemical - Mamman, Ajit Singh; Lee, Jong-Min; Kim, Yeong-Cheol; Hwang, In Taek; Park, No-Joong; Hwang, Young Kyu; Chang, Jong-San; Hwang, Jin-Soo (Biofuels Bioproducts & Biorefining-Biofpr, 2008)
Hemicellulose, the second, most common polysaccharide in nature constitutes approximately 20-35% of lignocellulosic biomass. Effective utilization of biomass, hitherto underutilized, is gaining tremendous importance for the production of energy, fuels, and chemicals. Amongst the vast array of chemicals derived from lignocellulosics, furfural is the key chemical that finds wide applications in oil refining, plastics, pharmaceutical and agrochemical industries. There is no synthetic route for the production of furfural. A few conventional technologies currently in practice for its separation and subsequent isolation are appropriately reviewed. Major disadvantages associated with processes currently used for the production of furfural based on acid-catalyzed hydrolysis have been discussed. A need to develop a process which is devoid of all the shortcomings associated with conventional process is emphasized. Several important aspects of chemistry underlying the acid hydrolysis of xylose are discussed. The importance of myriad pre-treatment steps involved to surmount the physical and chemical barriers and to liberate xylose from the confines of acid-resistant layer of lignin has been emphasized. New developments in the production of furfural from cyclodehydration of xylose using solid acid catalysts in the recent past have been reviewed appropriately in present communication. Finally, the production of furfural and furfuryl alcohol, their domestic market and export in China deserve some coverage and therefore have appropriately been discussed as well. (c) 2008 Society of Chemical Industry and John Wiley & Sons, Ltd
Keywords: acid hydrolysis; cyclodehydration; furfural; Hemicellulose; pre-treatment of lignocellulosics; Xylose